COMPARISON OF TOTAL SERUM ANTIOXIDANT CAPACITY BETWEEN MALE SMOKERS AND NONSMOKERS - Jayachandra, Srinivasa; Agnihotram, Gopinath (Pakistan Journal of Physiology, 2018)
Background: Smoking is characterized by the production of increased free radicals and oxidative stress. The objective of this study was to compare total antioxidant capacity between adult male smokers and nonsmokers. Methods: A total of 74 male subjects were involved in this study. Thirty-six of them were nonsmokers and another 38 of were smokers. Age of the smokers and nonsmokers were ranged between 30 and 45. Venous blood was collected from subjects after an overnight fast between 8:00 AM and 9:00 am. Blood samples were used for evaluation of serum total antioxidant capacity. Results: Data showed that total antioxidant capacity was significantly higher in smoker than non-smoker subject (p<0.05). There was no a significant correlation between the number of cigarettes smoked and the total antioxidant capacity (r= -0.137, p=0.673). Conclusion: Smoking reduces total antioxidant capacity which may put the smokers at risk of developing many oxidative stress related disorders. Pak J Physiol 2016;12(3):37–9